A 130 GHz Fully-Integrated Fundamental-Frequency D-Band Transmitter Module with > 4 dBm Single-Ended Output Power - Aguilar Mendoza, Erick; Issakov, Vadim; Weigel, Robert (2020 International Symposium on Circuits and Systems (ISCAS), 2020)
A 130 GHz fully integrated fundamental frequency transmitter (TX) module with 4.4 dBm single-ended measured output power in a 130 nm SiGe technology is presented. The transmitter achieves in measurement a phase noise of -88 dBc/Hz at 1 MHz offset frequency from a 130 GHz carrier and a tuning range of 17 GHz. Its relatively compact size, low power consumption and high output power, enables the TX module to be integrated into more complex D-Band transceiver modules for radar and imaging applications. Due to the available measurement equipment, it was only possible to measure the output power single-ended. The measured single-ended output power is 4.4 dBm. This corresponds well to a simulated differential output power of 8.1 dBm.Based on simulation results, the TX module can produce a maximum output power of 8.1 dBm. To the best of the author’s knowledge, the presented chip exhibits the highest output power fundamental frequency TX module among the recently reported state-of-the art chips in this frequency range. <br